2014
DOI: 10.1155/2014/876035
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile and Oxidative Stress Markers in Wistar Rats following Oral and Repeated Exposure to Fijk Herbal Mixture

Abstract: This study determined the effect of the oral and repeated administration of Fijk herbal mixture on rat biochemical and morphological parameters. Twenty-four Wistar rats were distributed into four groups of 6. Group A served as control and received oral administration of distilled water daily. The experimental groups B, C, and D were daily and orally exposed to Fijk herbal mixture at 15, 30, and 45 mg/kg, respectively. Treatments lasted for 21 days. The rats were sacrificed under mild diethyl ether anesthesia 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…In like manner, the present study showed that arsenite exposure has capacity to predispose rats to cardiovascular disorder by increasing plasma total CHOL, LDL-C, while lowering the HDL-C levels which raised the atherogenic index. Elevated atherogenic index has been associated with the development of atherosclerosis (Olukanni et al 2013;Adeyemi and Orekoya 2014). Our findings agree with studies that have linked arsenic toxicity to cardiovascular disorders (Straub et al 2008;Das et al 2012;Kumar et al 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In like manner, the present study showed that arsenite exposure has capacity to predispose rats to cardiovascular disorder by increasing plasma total CHOL, LDL-C, while lowering the HDL-C levels which raised the atherogenic index. Elevated atherogenic index has been associated with the development of atherosclerosis (Olukanni et al 2013;Adeyemi and Orekoya 2014). Our findings agree with studies that have linked arsenic toxicity to cardiovascular disorders (Straub et al 2008;Das et al 2012;Kumar et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Arsenic exposure in rats significantly reduced the rat liver weight as well as the liver-to-body weight ratio. This may indicate ensuing adverse effect by arsenite as studies have associated changes to body or organ weights with chemical or drug intoxication (Adeyemi and Orekoya 2014;Sulaiman et al 2015). This is consistent with other studies have demonstrated arsenic-induced changes to rat body or organ weights (Aliyu et al 2012;Chandraayagam et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that change to body or organ weights after chemical exposure may indicate toxicity[28–29]. In the present study, Ni exposure caused rat weight loss as well as alterations in vital organ weights in manners that may suggest ensuing adverse effect.…”
Section: Discussionsupporting
confidence: 58%
“…This is further supported by the plasma AST/ALT ratio of less than one (AST/ALT <1) which may indicate ensuing acute or chronic liver injury (Essani et al, 1995). This could be due the fact that cellular enzymes extrude into the extracellular fluid, thus raising their concentrations in plasma (Adeyemi and Bukola, 2014) due to hepatocellular damage, hence the rise in their plasma levels. The significant decrease in AST and ALT observed in groups C and D when compared with group B may be attributed to the antioxidative or the hepatoprotective effect of leaves aqueous extract of A. indica which is similar to documented reports on the hepatoprotective activity of A. indica (Ha et al, 2010).…”
Section: Discussionmentioning
confidence: 94%